Effect of Interactive Media-Assisted PjBL on Social Studies Concept Understanding Based on Students’ Learning Interest - I Kadek Tediana Saputra; I Gede Margunayasa; I Wayan Kertih (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study examined the effect of interactive media-assisted Project-Based Learning (PjBL) on elementary students' understanding of social studies concepts by considering their learning interest. A quantitative approach with a quasi-experimental design was employed involving 64 fifth-grade students from public elementary schools in North Denpasar, Bali. Data were collected using a validated social studies concept understanding test and a learning interest questionnaire. The data were analyzed through two-way ANOVA and Scheffé post hoc tests. The findings revealed that students taught using interactive media-assisted PjBL achieved significantly higher conceptual understanding than those receiving conventional instruction (F = 20.495, p < .001). Learning interest also significantly influenced conceptual understanding (F = 4.748, p = .034). However, no significant interaction was found between the learning model and learning interest (F = 1.947, p = .169), indicating that PjBL consistently improved conceptual understanding regardless of students' learning interest levels. These findings support integrating interactive media into project-based learning to enhance elementary social studies instruction.